The Legal Aspects of Importing Rice to Food Sovereignty in Indonesia - Nurul Nadia; Akhmad Farroh Hasan (Fakultas Syariah Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
The rice import policy that issued by the minister of trade with the consideration of the lack of rice supply became polemic because the policy was issued just before the harvest season arrived. This caused turmoil for the farmers who were disadvantaged by the rice import policy. This study aims to determine how rice imports should be carried out based on Law Number 18 of 2012 concerning Food and maslahah mursalah to the implementation of food sovereignty in Indonesia.This research was conducted using normative research methods using normative case studies in the form of legal behavior products. The study was conducted using a conceptual approach and the regulatory approach. The rice import policy that carried out by the government is deemed incompatible with the ideals of food sovereignty and the concept of maslahah mursalah. This happened because the policy makers do not look at the sustainability of farmers’ business and ignore their welfare. Rice imports cause losses for farmers and society in general. In addition, rice imports also have a negative impact on the country's economy.